Culture of Bovine Aortic Endothelial Cells in Galactose Media Enhances Mitochondrial Plasticity and Changes Redox Sensing, Altering Nrf2 and FOXO3 Levels - Leticia Selinger Galant; Laura Doblado; Rafael Radi; Andreza Fabro de Bem; Maria Monsalve (MDPI AG, 2024)
Understanding the complex biological processes of cells in culture, particularly those related to metabolism, can be biased by culture conditions, since the choice of energy substrate impacts all of the main metabolic pathways. When glucose is replaced by galactose, cells decrease their glycolytic flux, working as an in vitro model of limited nutrient availability. However, the effect of these changes on related physiological processes such as redox control is not well documented, particularly in endothelial cells, where mitochondrial oxidation is considered to be low. We evaluated the differences in mitochondrial dynamics and function in endothelial cells exposed to galactose or glucose culture medium. We observed that cells maintained in galactose-containing medium show a higher mitochondrial oxidative capacity, a more fused mitochondrial network, and higher intercellular coupling. These factors are documented to impact the cellular response to oxidative stress. Therefore, we analyzed the levels of two main redox regulators and found that bovine aortic endothelial cells (BAEC) in galactose media had higher levels of FOXO3 and lower levels of Nrf2 than those in glucose-containing media. Thus, cultures of endothelial cells in a galactose-containing medium may provide a more suitable target for the study of in vitro mitochondrial-related processes than those in glucose-containing media; the medium deeply influences redox signaling in these cells.